2018
DOI: 10.1152/ajpcell.00310.2017
|View full text |Cite|
|
Sign up to set email alerts
|

The role of microRNA-1 targeting of MAPK3 in myocardial ischemia-reperfusion injury in rats undergoing sevoflurane preconditioning via the PI3K/Akt pathway

Abstract: Recent studies have uncovered the vital roles played by microRNAs in regulating cardiac injury. Among them, the cardiac enriched microRNA-1 (miR-1) has been extensively studied and proven to be detrimental to cardiac myocytes. Hence, the current study aimed to explore whether miR-1 affects myocardial ischemia-reperfusion injury (MIRI) in rats undergoing sevoflurane preconditioning and the underlying mechanism. After successful model establishment, rats with MIRI were transfected with mimics or inhibitors of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…Notably, downregulation of MAPK3 by miR-15b is associated with ameliorated cardiomyocyte injury induced by hypoxia [14]. Hao et al [13] also showed that inhibition of miR-1 promotes MAPK3 to decrease myocardial ischemiareperfusion injury in rats undergoing sevoflurane preconditioning. Moreover, MAPK3 has been demonstrated to play a protective role in cardiomyocyte apoptosis [24].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Notably, downregulation of MAPK3 by miR-15b is associated with ameliorated cardiomyocyte injury induced by hypoxia [14]. Hao et al [13] also showed that inhibition of miR-1 promotes MAPK3 to decrease myocardial ischemiareperfusion injury in rats undergoing sevoflurane preconditioning. Moreover, MAPK3 has been demonstrated to play a protective role in cardiomyocyte apoptosis [24].…”
Section: Discussionmentioning
confidence: 97%
“…They are reported to regulate various cellular processes, such as proliferation and apoptosis [12]. MAPK3, also known as extracellular-regulated protein kinase 1 (ERK1), is reportedly upregulated after miR-1 knockdown with protective effects against myocardial ischemia-reperfusion injury in rats undergoing sevoflurane preconditioning [13]. MiR-15b was also found to reduce rat cardiomyocyte apoptosis by posttranscriptionally downregulating MAPK3 [14].…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K/AKT signaling pathway is considered as an endogenous negative-feedback regulatory mechanism that promotes cell survival in response to harmful external stimuli ( 26 ). Numerous previous studies have provided ample evidence suggesting that the PI3K/AKT signaling pathway may serve a critical role in the pathological progression of MIRI ( 27 – 29 ). The activated form of AKT, p-AKT, regulates numerous apoptosis-related mediators; for example, once activated, p-AKT acts on intrinsic cell death pathways through Bcl-2 family members (Bcl-2, Bcl-xl, Bax and Bad), as well as extrinsic cell death pathways through caspase family members (cleaved caspase-3, caspase-8 and caspase-9) ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…[48]. Inhibition of miR-1 was found protective against cardiac I/R injury also in rats likely via promoting MAPK3/PI3K/Akt signaling [56]. In a comparative study in young and old mice exposed to MI, increased levels of miR-1 were found in old mice post-MI in comparison to young ones, and this was associated with enhanced adverse cardiac remodeling, suggesting elevated levels of miR-1 as a predictive biomarker of high-risk of myocardial injury in older individuals [57].…”
Section: Role Of Mir-1 In Cardiac I/r Injurymentioning
confidence: 99%
“…↓miR-1 in heart tissue in response to I/R in rats, mice, and infarcted human hearts [48][49][50]52,53] ↓miR-1 in H9c2 cells and neonatal cardiac myocytes in response to H/R [48,51] ↑miR-1 in remote myocardium compared to infarcted zone or healthy hearts in infarcted human hearts [54] ↑levels of circulating miR-1 after AMI in pigs and humans [58,59] miR-1 overexpression exacerbated cardiac I/R injury in transgenic mice [55] miR-1 inhibition protects against I/R (H/R) injury in rats, mice, and H9c2 cells [48,55,56] miR-21…”
Section: Type Of Cvd Mir Findings Referencementioning
confidence: 99%